Diets and selected lifestyle practices of self-defined adult vegetarians from a population-based sample suggest they are more 'health conscious' - Barr Susan I; Bedford Jennifer L (BMC, 2005)
Abstract Background Few population-based studies of vegetarians have been published. Thus we compared self-reported vegetarians to non-vegetarians in a representative sample of British Columbia (BC) adults, weighted to reflect the BC population. Methods Questionnaires, 24-hr recalls and anthropometric measures were completed during in-person interviews with 1817 community-dwelling residents, 19-84 years, recruited using a population-based health registry. Vegetarian status was self-defined. ANOVA with age as a covariate was used to analyze continuous variables, and chi-square was used for categorical variables. Supplement intakes were compared using the Mann-Whitney test. Results Approximately 6% (n = 106) stated that they were vegetarian, and most did not adhere rigidly to a flesh-free diet. Vegetarians were more likely female (71% vs. 49%), single, of low-income status, and tended to be younger. Female vegetarians had lower BMI than non-vegetarians (23.1 ± 0.7 (mean ± SE) vs. 25.7 ± 0.2 kg/m2), and also had lower waist circumference (75.0 ± 1.5 vs. 79.8 ± 0.5 cm). Male vegetarians and non-vegetarians had similar BMI (25.9 ± 0.8 vs. 26.7 ± 0.2 kg/m2) and waist circumference (92.5 ± 2.3 vs. 91.7 ± 0.4 cm). Female vegetarians were more physically active (69% vs. 42% active ≥4/wk) while male vegetarians were more likely to use nutritive supplements (71% vs. 51%). Energy intakes were similar, but vegetarians reported higher % energy as carbohydrate (56% vs. 50%), and lower % protein (men only; 13% vs. 17%) or % fat (women only; 27% vs. 33%). Vegetarians had higher fiber, magnesium and potassium intakes. For several other nutrients, differences by vegetarian status differed by gender. The prevalence of inadequate magnesium intake (% below Estimated Average Requirement) was lower in vegetarians than non-vegetarians (15% vs. 34%). Female vegetarians also had a lower prevalence of inadequate thiamin, folate, vitamin B6 and C intakes. Vegetarians were more likely than non-vegetarians to consider various health conditions and food/nutrition concerns when choosing foods. Conclusion In this population-based study, evidence was obtained to indicate that vegetarians appear more 'health conscious' than non-vegetarians, although specific differences were not always consistent by gender. Additional population-based studies are required to determine if the observed gender differences exist in other populations.